2023
DOI: 10.1021/acscatal.2c05894
|View full text |Cite
|
Sign up to set email alerts
|

Metal and Metal Oxide Supported on Ordered Mesoporous Carbon as Heterogeneous Catalysts

Abstract: The evolution of model catalyst systems has experienced single-crystal surfaces of different transition metals and different crystal faces, two-dimensional systems with nanoparticles (NPs) deposited on a flat support surface, and threedimensional systems with NPs loaded into the high-surface-area supports such as ordered mesoporous materials. The latter two systems mimic the nanoparticle properties in industrial catalysts. Ordered mesoporous carbon (OMC) materials play unparalleled roles in catalysis, energy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 261 publications
0
18
0
Order By: Relevance
“…For three composite catalysts, the catalytic activities of both NC-NiSe 2 -12 and NC-NiSe 2 -48 are inferior to that of NC-NiSe 2 -24, indicating that much higher or lower NiSe 2 coverages do not favor the enhancement of catalytic activity. The above results prove that the incorporation of carbon matrix is essential to enhance the HER activity of NiSe 2 . In addition, the hierarchical pores involved in NC provide rich channels for the efficient transport of active species in the catalytic process of electrocatalysis, thereby significantly boosting the electrochemical performance …”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…For three composite catalysts, the catalytic activities of both NC-NiSe 2 -12 and NC-NiSe 2 -48 are inferior to that of NC-NiSe 2 -24, indicating that much higher or lower NiSe 2 coverages do not favor the enhancement of catalytic activity. The above results prove that the incorporation of carbon matrix is essential to enhance the HER activity of NiSe 2 . In addition, the hierarchical pores involved in NC provide rich channels for the efficient transport of active species in the catalytic process of electrocatalysis, thereby significantly boosting the electrochemical performance …”
Section: Resultsmentioning
confidence: 66%
“…The above results prove that the incorporation of carbon matrix is essential to enhance the HER activity of NiSe 2 . 45 In addition, the hierarchical pores involved in NC provide rich channels for the efficient transport of active species in the catalytic process of electrocatalysis, thereby significantly boosting the electrochemical performance. 46 To understand the intrinsic mechanism of high catalytic activity of NC-NiSe 2 -x, the HER kinetics are further studied by Tafel slopes, where a smaller value is indicative of faster reaction kinetics.…”
Section: Structural and Morphological Analysesmentioning
confidence: 99%
“…Among them, the HPN-2 showed both the largest pore volume (0.37 cm 3 /g) and pore size (3.46 nm). The large pore volume and wide pore were expected to provide accommodate space and pore channels to accommodate and accelerate the diffusion of ACT, and it was beneficial to enhance the adsorption . The results revealed that HPN-2 had the appropriate pore volume and pore size for ACT adsorption.…”
Section: Resultsmentioning
confidence: 97%
“…The term "responsive factor" typically refers to specific sensitive substances that undergo changes in response to external stimuli. For instance, photoresponsive materials commonly include polyvinylpyrrolidone [72,73] and TiO 2 , [74,75] electric-responsive materials encompass graphene, [76,77] carbon nanotubes, [78,79] and metal oxides, [80,81] while magnetic-responsive materials comprise Fe, Co, Ni, [82] as well as iron oxides (Fe 3 O 4 , [83,84] γ-Fe 2 O 3 [85,86] ), among others. Noteworthy external environmental stimuli include light, electricity, and magnetism.…”
Section: Smart Responsive Superhydrophobic Mechanismmentioning
confidence: 99%